The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.17240/aibuefd.2018.18.37322-431426
|View full text |Cite
|
Sign up to set email alerts
|

Eği̇ti̇m Bi̇li̇mleri̇ Alanindaki̇ Li̇sansüstü Tezlerde Varsayim Kullanimi

Abstract: Bu araştırmanın amacı, Eğitim Bilimleri alanında yayınlanmış, lisansüstü tezlerin, ilgili istatistiksel analize dayalı olarak, sahip oldukları varsayımların test edilme durumlarının değerlendirilmesidir. Betimsel araştırma modelinde olan bu çalışmada, Türkiye'de 2015, 2016 ve 2017 (Eylül ayına kadar) yıllarında Eğitim Bilimleri Enstitüleri tarafından yayınlanmış ve Ulusal Tez Merkezi üzerinden erişimine izin verilmiş 95 lisansüstü tez incelenmiştir. Araştırmacılar tarafından hazırlanan tez inceleme formu ile t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This study examined the 275 articles and the findings demonstrated that most of the articles didn't claim about the structure of variables and assumptions they need to check. Başman et al (2018) examined the thesis in educational science and found that graduate students tend to check sample size correctly; however, normality and homogeneity of variances are still problematic. Furthermore, more than half of the graduate theses didn't provide the evidence of assumption checking for normality, homogeneity of variance, multicollinearity, autocorrelation, and linear relation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study examined the 275 articles and the findings demonstrated that most of the articles didn't claim about the structure of variables and assumptions they need to check. Başman et al (2018) examined the thesis in educational science and found that graduate students tend to check sample size correctly; however, normality and homogeneity of variances are still problematic. Furthermore, more than half of the graduate theses didn't provide the evidence of assumption checking for normality, homogeneity of variance, multicollinearity, autocorrelation, and linear relation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study showed that researchers applied unpaired t-test to pair groups in experimental design (Jaykaran, 2010). Besides that, assumption checking, and usage of parametric tests can be problematic in educational research (Başman, Uluman & Tunç, 2018;Demir, Saatçioğlu & İmrol, 2016;Evrekli, İnel, Deniş & Balım, 2011;İlhan, 2016;Jaykaran, 2010;Kabaca & Erdoğan, 2007). Specifically, it was identified that some of the researchers preferred parametric tests to non-normal distribution (Evrekli et al, 2011;Jaykaran, 2010), improper statistical methods for categorical data (Erdoğan, 2001), and univariate statistical tests when they had more than one dependent variable (Kabaca & Erdoğan, 2007).…”
Section: Introductionmentioning
confidence: 99%